Notch signaling mediated repressive effects of resveratrol in inducing caspasedependent apoptosis in MCF-7 breast cancer cells: Resveratrol as Notch signaling modulator - Pandey, Pratibha; Ramniwas, Seema; Seifeldin, Sara A; Alshaghdali , Khalid; Alharazi , Talal; Acar , Tolgahan; Upadhye, Vijay Jagdish; Sharma , Nishesh; Khan, Fahad; Saeed , Amir (Cellular and Molecular Biology, 2024)
Resveratrol, a potent anticancer bioactive compound, has been shown to trigger apoptosis in numerous cancer cells. Although Notch signaling promotes breast cancer apoptosis, it is unclear whether resveratrol induces apoptosis in MCF-7 cells via influencing the Notch pathway. This study aimed to evaluate the effect of resveratrol on modulating Notch signaling targets and provide critical information for employing resveratrol in breast cancer therapy. Thus, in this study, we have deciphered the effect of resveratrol against three potent genes (Notch1, Jagged1, and DLL4) of the notch signaling pathway. For mechanistic studies, in silico, and in vitro analysis was executed to investigate the apoptotic-inducing potential of resveratrol against three selected oncogenes involved in the progression of breast cancer. Docking analysis revealed the inhibitory potential of resveratrol against all three selected targets of the Notch pathway (Notch1: -5.0; Jagged-1: -5.9; DLL4: -5.8). In vitro, findings further displayed a significant reduction in cell viability in resveratrol-treated MCF-7 cancer cells, which were concomitantly related to the downregulation of Notch-1, Jagged-1, and DLL4. Moreover, the antiproliferative efficacy of resveratrol was correlated with apoptosis and modulation in the expression of Bax, Bcl-2, cyclin D1, CDK4, p21, and caspase-3 activation. Taken together, these experimental findings suggested that apoptotic inducing potential of resveratrol was mediated through a novel mechanism involving suppression of the Notch signaling pathway.